Indicadores básicos e desempenho da justica estadual de primeiro grau no Brasil - Alexandre Samy de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper offers a quantitative evaluation of the productive efficiency of state courts of first degree in Brazil, based on the stochastic frontier approach [Aigner D.J. (1977), Meeusen W (1977) and Battese and Corra (1977)]. This study exploits the novel database by the Conselho Nacional de Justica, which contains production reports for 8,495 state courts of first degree. The inputs in the production function of jurisdictional services include judges - weighted by their experience in judicature - and staff as well as pending cases. The technical inefficiency of courts depends on a vector of court characteristics - the types of cases handled and the type of relationship of judges and staff personnel with the court - and 'environment' variables such as: geography and the classification of the jurisdiction (comarca); and the quality of judicial administration at the local level, proxied by the status of local notary and registry services (privatized versus official). Finally, court performance is also influenced by socioeconomic and political covariates, which potentially shift the demand for jurisdictional services. Estimates of the model allow testing some standard hypotheses in the literature on court performance. Moreover, the model provides a sophisticated assessment of the performance of state judiciaries, resulting in policy recommendations towards judicial administration of state courts in Brazil.
Keywords: D24; D73; H49; K40; 330